2007
DOI: 10.1016/j.ygeno.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the human BDNF locus: Bidirectional transcription, complex splicing, and multiple promoters

Abstract: Brain-derived neurotrophic factor (BDNF), a member of the nerve growth factor family of neurotrophins, has central roles in the development, physiology, and pathology of the nervous system. We have elucidated the structure of the human BDNF gene, identified alternative transcripts, and studied their expression in adult human tissues and brain regions. In addition, the transcription initiation sites for human BDNF transcripts were determined and the activities of BDNF promoters were analyzed in transient overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
551
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 621 publications
(584 citation statements)
references
References 40 publications
8
551
2
4
Order By: Relevance
“…These promoters were targeted because they generate the majority of BDNF in the brain Pruunsild et al, 2007). Targeting was accomplished by genetically engineering the placement of an eGFP-STOP cassette upstream of the respective 5′-UTR splice donor site of the targeted exon (Supplementary Figure S1a) with a floxed PGK-Neo cassette inserted antisense to eGFP-STOP for selection.…”
Section: Disruption Of Bdnf Production From Specific Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…These promoters were targeted because they generate the majority of BDNF in the brain Pruunsild et al, 2007). Targeting was accomplished by genetically engineering the placement of an eGFP-STOP cassette upstream of the respective 5′-UTR splice donor site of the targeted exon (Supplementary Figure S1a) with a floxed PGK-Neo cassette inserted antisense to eGFP-STOP for selection.…”
Section: Disruption Of Bdnf Production From Specific Promotersmentioning
confidence: 99%
“…To determine the biological significance of this 'multiple promoter, same protein' mechanism, we generated four transgenic mouse lines in which BDNF production is selectively disrupted from one of the four major promoters I, II, IV, or VI (Bdnf-e1, -e2, -e4, and -e6 mice). We targeted transcripts containing 5′-untranslated region (5′-UTR) exons I, II, IV, and VI, because they constitute the majority of BDNF mRNAs produced in the brain Pruunsild et al, 2007). As BDNF production is only impaired from a single promoter, these models allow us to assess how loss of BDNF from one promoter vs another results in different consequences at the molecular, cellular, and behavioral levels.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple BDNF transcripts are generated by alternative splicing of one 5Ј exon with a shared 3Ј exon containing the entire BDNF coding region and either a short or long 3Ј UTR sequence (5,6). In recent studies, we have demonstrated that BDNF transcripts differ in their subcellular localization (7).…”
mentioning
confidence: 99%
“…3 Of these variants, BDNF-IV is the most commonly studied and its expression changes have been associated with behavioural phenotypes, psychiatric disorders and epigenetic modifications. 4 The promoter region in exon-IV contains specific binding sites for the cyclic-AMP-responsive-elementbinding protein (CREB) 5 and the methyl-CpG-binding-protein-2 (MeCP2) 6 making it a preferential candidate for epigenetic regulation.…”
mentioning
confidence: 99%